Vocational Training Preparation : a new concept of vocational preparation for learning impaired and socially disadvantaged young people - Zielke, Dietmar [Verfasser] (My University, 2007)
"Vocational preparation schemes are in a state of upheaval. The present public employment services measures will merge into three qualification levels of a new concept. Up to now the legislators have formulated clearly delineated guidelines for vocational preparation schemes as an integral part of the Vocational Education and Training Act (BBiG) and introduced a new term for them, Vocational Training Preparation. This article will show some of the differences between Vocational Training preparation and the new concept of the public employment services. It will show some of the reasons for the existing differences and at the same time indicate some of the preconditions for resolving them." (BIBB)
Erstveröffentlichung der englischen Version des Artikels in: BWP Special Edition 2005, S. 22-26
Keywords: S 1.2 Berufsvorbereitung; P 1.1 Jugendliche; P 1.7 Benachteiligte; S 1.2.1 Außerschulische Maßnahmen der Berufsvorbereitung; Berufsvorbereitung; Berufsausbildungsvorbereitung; Benachteiligter Jugendlicher; Qualifizierungsbaustein; Berufsbildungsrecht